2019
DOI: 10.1016/j.heliyon.2019.e02467
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity light treatment improves purple kale (Brassica oleracea var. sabellica) postharvest preservation at room temperature

Abstract: Purple Kale is a vegetable of the Brassicaceae family whose are popularly consumed in recent years due to their high level of healthy components. For consumption, matures leaves are harvested and postharvest senescence is induced. Changes in color leaves due to chlorophyll degradation are the main visible symptoms of postharvest senescence, but there are other changes that affect the nutritional quality of kale. The aim of this study was to investigate if low intensity light pulses could be used to delay posth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
3
8
2
7
Order By: Relevance
“…The effect of light intensity and/or light spectral quality on shelf life, quality, and phytochemical content in post-harvest Brassica vegetables has been investigated [58][59][60][61][62][63]. In this regard, low-intensity light treatment during storage improves the appearance and quality of kale, broccoli, and pak choi by maintaining the chlorophyll content and activating photosynthesis [58,59,63]. In the same way, antioxidants, monosaccharides, and starch were retained in Chinese kale leaves after a treatment with low-intensity continuous light during post-harvest storage [60].…”
Section: Post-harvest Life Of Brassica Vegetables and Circadian Clockmentioning
confidence: 99%
“…The effect of light intensity and/or light spectral quality on shelf life, quality, and phytochemical content in post-harvest Brassica vegetables has been investigated [58][59][60][61][62][63]. In this regard, low-intensity light treatment during storage improves the appearance and quality of kale, broccoli, and pak choi by maintaining the chlorophyll content and activating photosynthesis [58,59,63]. In the same way, antioxidants, monosaccharides, and starch were retained in Chinese kale leaves after a treatment with low-intensity continuous light during post-harvest storage [60].…”
Section: Post-harvest Life Of Brassica Vegetables and Circadian Clockmentioning
confidence: 99%
“…Traditionally, vegetable crops are transported and stored in the dark, which promotes senescence (Song et al, 2020). Previous studies have shown that light treatment could combat the senescence induced by constant darkness (Bárcena et al, 2019;Song et al, 2020). Light irradiation could maintain the quality of various vegetables, such as bok choy (Song et al, 2020;Zhou et al, 2020), Brussels sprouts (Hasperué et al, 2016), purple kale (Bárcena et al, 2019), basil (Costa et al, 2013), and broccoli (Bárcena et al, 2020;Favre et al, 2018;Jin et al, 2015;Loi et al, 2019) during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Se han reportado numerosos efectos de la aplicación de tratamientos con luz blanca, desde la diminución en la pérdida de peso y pardeamiento en lechuga (Charles et al, 2018), retención de azúcares, capacidad antioxidante y clorofilas en kale (Bárcena et al, 2019), retención de proteínas, azúcares y clorofilas en albahaca (Costa et al, 2013) y conservación del contenido de ácido ascórbico en espinaca (Gergoff Grozeff et al, 2013). También se han observado acumulación de antocianinas y compuestos fenólicos en higos (Rodov et al, 2012), frutillas (Xu et al, 2014) y cerezas (Kokalj et al, 2019).…”
Section: Tratamientos Con Luz Blancaunclassified
“…Asimismo, muchas de las hortalizas luego de ser cosechadas continúan siendo fotosintéticamente activas, es por todo esto que la luz puede tornarse en un factor muy influyente en la vida poscosecha de las frutas y hortalizas. Diversos estudios llevados a cabo en kale (Bárcena, Martínez and Costa, 2019), espinaca (Gergoff Grozeff, Chaves and Bartoli, 2013), albahaca (Costa et al, 2013) y lechuga (Charles et al, 2018), entre otros, demostraron un retraso en la senescencia y conservación del color verde debido a tratamientos con pulsos de luz visible. En base a estudios previos realizados por el grupo de trabajo en brócoli (Büchert et al, 2010; Agustín M. Büchert, Civello and Martínez, 2011) donde se observaron además cambios en la expresión génica, se decidió evaluar el efecto de un tratamiento con luz visible sobre la expresión de los genes BoNYC1, BoNOL y BoHCAR de la vía de degradación de clorofilas.…”
Section: Tratamiento Con Luz Blancaunclassified
See 1 more Smart Citation